Conhecimentos Bakairi cotidianos e conhecimentos químicos escolares : perspectivas e desafios - Lopes, Edinéia Tavares (2012)
This research deals with the possibilities and challenges found towards the realization of the Teaching of Chemistry in the context of Indigenous School Education with the Bakairi of the Aturua Village in the State of Mato Grosso. From the understanding of how the Bakairi had a proper grasp of school and of the idea of culture, we aim at understanding, at first, the relation the group being observed maintains with school and school knowledge and, then, focussing on the reality concerning the Teaching of Chemistry in such a context. In order to come to conclusions in the present research, we counted on the definition of culture by Geertz. Based on Bakhtin s propositions, we aimed at understanding how the speech act occurs and how the meaning of the speech acts of the students being investigated is constructed. We also counted on the notion of relation with knowledge, proposed by Charlot, and with the notion of rupture and epistemological obstacles, proposed by Bachelard. As to the characterization of scientific language, more specifically the chemical language, the definitions proposed by Mortimer were the ones employed. The notion of enculturation was also based on Mortimer s propositions. The data was collected through observations, drawings, individual and collective interviews. Based on these theoretical assumptions, we analyzed the different explanations given by High School students to themes explained by Science as chemical transformations. Fishing with timbó vine was chosen to do so. More specifically, we aimed at understanding, at first, how the discourses of the indigenous quotidian and the ones of science/school appeared and had a dialogue towards the production of what the subjects that take part in the research said. We aimed at identifying the challenges and possibilities towards the construction of school chemical knowledge. In this respect, it can be said that the relation these students and other members of the community maintain with school is associated with the idea of learning how to be someone and school knowledge is mainly placed towards the relation with the non-indigenous knowledge. Most pieces of information given at school are not questionable in their validation field: school environment, the white space. School chemical knowledge is worked according to the logic of didactic books, which brings, as a consequence, the gap between chemical knowledge and quotidian bakairi knowledge. Such a gap and the logic of didactic books lead towards the creation of obstacles instead of enabling students to learn school chemical knowledge. Students discourses, on their turn, showed the necessity of searching for new forms of explaining fishing with timbó vine and the action of the poison, which go beyond pragmatic explanations and the ones connected with mythological aspects. To do so they marked the area of validation of each explanation. To explain fishing with timbó vine and the action of the poison, students turned to their quotidian knowledge and the language which was characteristic of their cultural dimension, which, so far, have been enough when it comes to the explanation and realization of such an activity. However, this language and the conceptual tools which are made available for students by the school are not able to explain such phenomena, from the viewpoint of convergence with scientific explanation. It can be concluded that school chemical knowledge is very distant from the quotidian existence of these students. Based on their discourses, possible obstacles are shown in this teaching modality when it comes to the teaching of school chemical knowledge, but possibilities which can promote a process of teaching which contributes to have students access such a cultural dimension are also revealed.